The Effect of Mung Bean Flour Addition on the Organoleptic Properties, Nutritional Content, and Acceptability of Mung Bean Cassava Cake (Bosikajo) as a Snack for People with Type 2 Diabetes - Hernisa Widiatri; Made Darawati; Reni Sofiyatin; I Gde Narda Widiada; Binardo Adi Seno Mawarno (Jurnal Gizi Prima (Prime Nutrition Journal), 2026)
Background: The use of local foods in the development of functional foods is crucial for promoting food diversification and managing degenerative diseases, such as type 2 diabetes. A combination of mung bean flour and cassava flour can produce products with a low glycemic index and high fiber and protein content.. Research Methods: This experimental study used a one-factor completely randomized design (CRD) with five treatments (addition of mung bean flour at 25 g, 50 g, 75 g, 100 g, and 125 g) and three replicates. A total of 25 semi-trained panelists were involved in the organoleptic testing, while  nutrient content analysis was conducted using the proximate method, and acceptability testing was performed on 30 patients with type 2 diabetes aged 50–64 years. Research Results: The results show that treatment t3 (75 g mung bean flour) had the highest hedonic scores (color 4.1; aroma 4.2; taste 4.3; texture 4.4). The nutritional content of treatment T3 cake per 100 g is as follows: energy 286 kcal, protein 9.15%, fat 9.20%, carbohydrates 43.13%, fiber 4.82%, moisture 29.35%, and ash 2.35%. The acceptability rate reached 86.7% and falls into the “good” category. Conclusion:  The addition of 75 g of mung bean flour produces a cake with the best organoleptic and nutritional quality and is acceptable to patients with type 2 diabetes as a healthy and functional snack.